THE EFFECT OF CONCENTRATION AND DIFFERENT SOAKING TIME ON STARFRUIT (Averrhoa bilimbi L) SOLUTION TO THE HEAVY METAL (Pb AND Cd) CONTENT OF BARNACLE (Pilsbryoconcha exilis) - Jayanti, Tinneke Dwi; Ilza, Mirna; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was aimed to determine the exact concentration and soaking time to reduce the heavy metals Pb and Cd of barnacle (Pilsbryoconcha exilis). The experimental method was used in this research with Factorial Completely Randomized Design. There were 3 treatment levels of starfruit solution concentrations 10% (K1), 15% (K2), and 20% (K3), with 2 treatment levels of soaking time 60 minutes (W1) and 90 minutes (W2). All samples were assessed for chemical contents, metal content Pb and Cd, and organoleptic.The chemical contents of fresh barnacle include water 84.10% (ww), ash 11.06% (dw), protein 59.09% (dw), fat 7.79% (dw) and carbohydrate (by difference) 22.07% (dw). The result showed that the treatment of soaking the barnacle into the 20% of starfruit solution for 90 minutes was the best treatment, whereas the reduction of heavy metal of Pb 72.30% and 15% of starfruit solution for 90 minutes was the best treatment, whereas the reduction of heavy metal of Cd 67.64%. The soaking of barnacle into the starfruit solution was significantly affect tothe organoleptic quality, included appearance, odor, and texture. The higher concentration and longer soaking timewas given cause the barnacle tobe white and not brilliant, the odor was very fresh and the texture was less dense and slighlty soft.Keywords:barnacle, concentration, soaking time, heavy metal